Criminal Responsibility of the Pharmacist in the Pharmaceutical Services in Indonesia - Latu, Saparuddin; K, Aswanto; Arie, Marthen; Alimuddin, Alimuddin (Pharmaceutical Reports, 2022)
Medical malpractice has a long history in Indonesia, with fatal consequences for patients due to negligence from the health practitioner. This study aims to ensure legal certainty in pharmaceutical practice according to laws and regulations. Also, to provide criminal law sanctions for pharmacists in pharmaceutical practices that lead to criminal acts. The method used was qualitative empirical normative research with a literature study. This research was conducted qualitatively based on data triangulation which resulted from three ways: interview, participant to observation, and review of organizational records (document records). Data collection usually uses qualitative research observation, documentation, and interview methods. This study discusses legal provisions related to health and pharmaceutical services and interviews with ten people at Dr. Wahidin Sudirohusodo Regional General Hospital, Makassar, and five people from Wamena Regional General Hospital, Jayawijaya Regency, Papua. Our study exhibited that implementing a pharmacist's practice was based on the prevailing laws and regulations. The pharmaceutical practice in question starts from planning, procurement, storage, distribution, evaluation, and provision of drug information and monitoring of drug side effects. These practices are based on Government Regulation No. 51 of 2009 article 4. This regulation is stated to protect patients and the public in obtaining and stipulating pharmaceutical preparations and pharmaceutical services. In addition, to maintain and improve the quality of implementation of pharmaceutical work by using developments in science and technology as well as laws and regulations; and provide legal certainty for patients, communities, and pharmaceutical workers. In the criminal responsibility of pharmacists in pharmaceutical services that have resulted in illegal acts, there have not been cases that have reached court proceedings. Nevertheless, there are cases where actions that have resulted in criminal acts have occurred in the field. Still, mediation can resolve them to reach a consensus with unique mediation.